Efeito do treinamento combinado sobre a composição corporal e biomarcadores de função renal em pacientes transplantados renais: um ensaio clínico controlado e randomizado - LIMA, Paulo Soares (2020)
Objective: To evaluate the effect of combined training on body composition and renal function biomarkers in kidney transplant patients. Materials and Methods: After being released by the responsible nephrologist, kidney transplant patients were invited to participate in the study and later answered the International Physical Activity Level Questionnaire and the Clinical Interview Questionnaire / Anamnesis. Then, they underwent a physical evaluation consisting of 1) anthropometry and body composition (Plethysmography) 2) renal function biomarkers obtained from patient records (Urea, Uric Acid, Creatinine and Glomerular Filtration Rate); 3) bioelectrical impedance vector analysis (Bioimpedance); 4) serum electrolytes obtained from patients' medical records (Calcium, Sodium, Potassium and Phosphorus); 5) handgrip strength (Portable Dynamometry); 6) aerobic capacity (six-minute walk test). After all these steps, the patient was blindly allocated according to the previous randomization between two groups: (a) aerobic training combined with resistance training in the same session; (b) usual care. The training program was carried out three times a week for 12 weeks. After the intervention, all volunteers were reevaluated following the same protocols previously performed. 12 kidney transplant patients (49 ± 13 years) completed the study, seven of whom belonged to the experimental group (4 women and 3 men, 54 ± 4 years) and five to the control group (5 women, 43 ± 18 years). The normality of the data was tested (ShapiroWilk) and the adjusted mean differences between the groups were calculated (linear mixed models). Results: The combined training mediated improvements on fat percentage (Δ = -2.5%; p = 0.012), lean mass percentage (Δ = 2.2%; p = 0.013), serum creatinine (Δ = -0, 5 mg / dL); p = 0.005), glomerular filtration rate (Δ = 27.7 mL / min / 1.73 m2; p = 0.004), serum urea (Δ = -17.6 mg / dL); p = 0.009), total serum calcium (Δ = 1.0 mg / dL); p <0.001), serum sodium (Δ = -7.3 mmol / L); p = 0.015), serum potassium (Δ = -1.4 mmol / L; p <0.001) and VO2peak (Δ = 2.6 mL / min / kg; p = 0.003). However, there were no changes in the bioelectrical impedance vector analysis and handgrip strength (p> 0.05). Conclusion: Improvements were observed in body composition markers, renal function biomarkers, serum electrolytes and aerobic capacity. For this reason, this type of approach is suggested as a strategy for maintaining or improving the health of renal transplant patients and, consequently, the survival of the renal graft.